2004
DOI: 10.1103/physreve.70.031303
|View full text |Cite
|
Sign up to set email alerts
|

Slowly sheared dense granular flows: Crystallization and nonunique final states

Abstract: Simultaneous time-resolved measurements of internal structure, granular volume, and boundary shear force are reported for dense granular packing steadily sheared under a fixed normal load. We identify features of the crystallization transition for a deep shear flow, whose height-dependent local mean velocity spans more than five orders of magnitude. This structural change is accompanied by a significant decrease of granular volume and shear force, with a more rapid falloff of particle velocity with depth than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 43 publications
(75 reference statements)
5
39
1
Order By: Relevance
“…Such effects are particularly strong in two dimensional studies [43], and this plays a much weaker role in three-dimensional situations, where there is more geometrical freedom. For example, Tsai and Gollub [37] showed that crystallization in 3D monodisperse packings would only occur after many hours of shearing. To check the effect of particle size, a drainage simulation was carried out using model F using particle diameters uniformly distributed over 0.95d to 1.05d.…”
Section: Polydispersitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such effects are particularly strong in two dimensional studies [43], and this plays a much weaker role in three-dimensional situations, where there is more geometrical freedom. For example, Tsai and Gollub [37] showed that crystallization in 3D monodisperse packings would only occur after many hours of shearing. To check the effect of particle size, a drainage simulation was carried out using model F using particle diameters uniformly distributed over 0.95d to 1.05d.…”
Section: Polydispersitymentioning
confidence: 99%
“…A dye added to the liquid is illuminated by a light sheet of thickness less than 0.1d and imaged from an orthogonal direction using a 512 × 480 pixel resolution CCD camera, where 20 pixels corresponds to one d. The particles in an image appear dark against a bright background with a flat intensity profile across each particle. We then make use of convolution procedure [37] to convert each image into a 2D map consisting of bright sharp peaks of intensity corresponding to particle centers which are then obtained using a centroid algorithm [38]. This procedure yields particle position in every image to within a twentieth of a particle diameter.…”
Section: A Index-matching Experimentsmentioning
confidence: 99%
“…Many experiments have been done on drainage flows in quasi-2d silos where particles are tracked accurately at a transparent wall [9,14,15,16,27]. Some three-dimensional particle tracking in granular materials and colloids has also been done with magnetic resonance imaging [28], confocal microscopy [29], index matching with an interstitial fluid [30], and diffusing-wave spectroscopy [31], although these systems are quite different from a pebble-bed reactor core. Experimental studies of more realistic geometries for PBR have mostly focused on the porosity distribution of static packings of spheres [32,33], which affects helium gas flow through the core [34,35,36].…”
Section: Introduction a Backgroundmentioning
confidence: 99%
“…Granular materials exhibit many complex phenomena [11,12]. The ordering of monodisperse granular materials, when subjected to vibration or shear flow, is one example [13][14][15][16][17][18]. The transition from a disordered state to an ordered state is marked by a significant increase in the solid fraction manifested as a compaction of the material [13,17].…”
mentioning
confidence: 99%